Impact of Methanol and Glycine Betaine on Yield and Quality of Fodder Beet Genotypes (Beta vulgaris subsp. vulgaris) - Pezhman Haghighi; Davood Habibi; Hamid Mozafari; Behzad Sani; Mehdi Sadeghishoae (Agronomy, 2021)
Two field experiments were carried out during 2018–2019 at the Hamedan and Qom sites, which are different ecological locations of Iran. Hamedan was selected as a temperate climate and Qom as semi-arid to study some of the morphological and physiological traits of fodder beet in various climatic conditions. The experimental map was designed as a split–split-plot in the form of a randomized complete block with three replications. The main plots were assigned three levels of methanol (i.e., control, 15, and 30% by volume). The sub-plots were restricted to two glycine betaine (GB) concentrations (i.e., control and four grams per liter of methanol consumed, and the sub-sub-plots consisted of six different genotypes of fodder beet). The results showed that root length, root and foliage yield/ha, as well as sugar content increased with the incremental level of methanol and/or GB concentration. Foliar application of methanol and GB also significantly changed the qualitative parameters including sodium content, catalase value, crude protein percentage, and dry matter digestibility. It should be noted that two sites differed in most of the investigated traits, so that Hamedan treatment had a more active role on fodder beet growth, yield, and quality compared with Qom. Meanwhile, there was a significant difference between fodder beet genotypes. Generally, spraying fodder beet with 15%by volume methanol or GB with concentration of four grams per liter of methanol is the recommended treatment for raising forage yield under the ecological circumstances of this research.